Dietary glucosinolates derived isothiocyanates: chemical properties, metabolism and their potential in prevention of Alzheimer's disease - Farhana Khan; Abhishek Joshi; Hari Prasad Devkota; Vetriselvan Subramaniyan; Vinoth Kumarasamy; Jaya Arora (Frontiers Media S.A., 2023)
Alzheimer's disease (AD) is the most prevalent form of dementia affecting millions of people worldwide. It is a progressive, irreversible, and incurable neurodegenerative disorder that disrupts the synaptic communication between millions of neurons, resulting in neuronal death and functional loss due to the abnormal accumulation of two naturally occurring proteins, amyloid β (Aβ) and tau. According to the 2018 World Alzheimer's Report, there is no single case of an Alzheimer's survivor; even 1 in 3 people die from Alzheimer's disease, and it is a growing epidemic across the globe fruits and vegetables rich in glucosinolates (GLCs), the precursors of isothiocyanates (ITCs), have long been known for their pharmacological properties and recently attracted increased interest for the possible prevention and treatment of neurodegenerative diseases. Epidemiological evidence from systematic research findings and clinical trials suggests that nutritional and functional dietary isothiocyanates interfere with the molecular cascades of Alzheimer's disease pathogenesis and prevent neurons from functional loss. The aim of this review is to explore the role of glucosinolates derived isothiocyanates in various molecular mechanisms involved in the progression of Alzheimer's disease and their potential in the prevention and treatment of Alzheimer's disease. It also covers the chemical diversity of isothiocyanates and their detailed mechanisms of action as reported by various in vitro and in vivo studies. Further clinical studies are necessary to evaluate their pharmacokinetic parameters and effectiveness in humans.